Neuron-macrophage crosstalk in the intestine: a ‘microglia’ perspective - Verheijden, Simon; De Schepper, Sebastiaan; Boeckxstaens, Guy E. (Frontiers in Cellular Neuroscience, 2015)
Intestinal macrophages are strategically located in different layers of the intestine, including the mucosa, submucosa and muscularis externa, where they perform complex tasks to maintain intestinal homeostasis. As the gastrointestinal tract is continuously challenged by foreign antigens, macrophage activation should be tightly controlled to prevent chronic inflammation and tissue damage. Unraveling the precise cellular and molecular mechanisms underlying the tissue-specific control of macrophage activation is crucial to get more insight into intestinal immune regulation. Two recent reports provide unanticipated evidence that the enteric nervous system acts as a critical regulator of macrophage function in the myenteric plexus. Both studies clearly illustrate that enteric neurons reciprocally interact with intestinal macrophages and are actively involved in shaping their phenotype. This concept has striking parallels with the central nervous system (CNS), where neuronal signals maintain microglia, the resident macrophages of the CNS, in a quiescent, anti-inflammatory state. This inevitably evokes the perception that the ENS and CNS share mechanisms of neuroimmune interaction. In line, intestinal macrophages, both in the muscularis externa and (sub)mucosa, express high levels of CX3CR1, a feature that was once believed to be unique for microglia. CX3CR1 is the sole receptor of fractalkine (CX3CL1), a factor mainly produced by neurons in the CNS to facilitate neuron-microglia communication. The striking parallels between resident macrophages of the brain and intestine might provide a promising new line of thought to get more insight into cellular and molecular mechanisms controlling macrophage activation in the gut.